Strategi Penyuluhan Pengendalian Hama Tikus yang Efektif untuk Petani di Desa Jombok, Ngantang Kabupaten Malang - Farah Mutiara; A. Yusuf Kholil; Fendiyatmi Kusufa; Tirta Yoga; Retno Ayu Dewi Novitawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Rice is a primary commodity in Indonesia's agricultural sector, playing a strategic role in national food security. However, rice productivity in Jombok Village, Ngantang District, Malang Regency, has declined due to an infestation of rats (Rattus argentiventer). The uncontrolled rat population has caused damage to crops from the vegetative to the generative stages, resulting in a decrease in harvest yields. The limited understanding among farmers about effective pest control strategies has worsened the situation. The community service aims to enhance farmers' knowledge and skills in controlling rat pests through an Integrated Pest Management (IPM) approach. The methods used include socialization, counseling, field training, and the evaluation of pest control techniques involving mechanical, biological, and chemical methods. Evaluation results showed that farmers' understanding improved from 40% to 85% after the training. Furthermore, after one month, the rat population decreased by 40%. These findings suggest that education and hands-on practice contribute to the effectiveness of pest control and increased rice productivity. Therefore, a farmer empowerment-based approach should continue to be implemented to support the sustainability of agriculture in agrarian regions.